LITERASI SAINS SISWA SEKOLAH DASAR MELALUI PENDEKATAN PEMBELAJARAN MENDALAM (DEEP LEARNING) - Dzuhrotul Ulumiyah; Maya Adina Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted based on the low level of science literacy among elementary school students, which is mainly caused by learning activities that emphasize memorization rather than critical thinking and meaningful understanding of scientific concepts. The purpose of this research is to analyze the implementation of the deep learning approach to improve science literacy among elementary school students. This study employed a qualitative approach with a case study design, involving one teacher and 20 fifth-grade students from a public elementary school in Kutai Barat Regency. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that the deep learning approach improves students’ science literacy in three main aspects: conceptual understanding, scientific process skills, and scientific attitudes. Students became more active, reflective, and able to relate scientific concepts to real-life situations. In addition, this approach fostered curiosity, collaboration, and deeper engagement in learning. Therefore, the deep learning approach is considered effective in developing meaningful and contextual science learning, which supports the enhancement of science literacy competencies in line with 21st-century learning goals.